Optimizing Aggressive Strategies as Adaptive Action for Rural Banks in Facing Competition In The Digital Banking Era - Septa Wihara, Dhiyan; Soeprajitno, Edy Djoko; Kholidi Hadi, Hafid; Amelia, Ratih (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
Rural Banks will identify their internal strengths to be able to seize opportunities to become opportunities for growth as well as in facing threats in the current banking digitalization era. This study aims to formulate a sustainable competitive strategy at PT. BPR X in Jombang Regency, East Java Province using SWOT analysis (Strength, Weakness, Opportunity and Threats). It is hoped that the results of this study can be used as a reference for Rural Banks to compete and build sustainable competitive advantages and contribute to strategic management, especially analysis of the company's internal and external environment. This study uses a qualitative approach with 2 informants, The instrument used is structured interviews. Then the interview results are integrated into the SWOT matrix to be weighted. After that, calculating the difference in each SWOT component and integrating it into a diagram so that you meet the strategic categories according to the difference calculation earlier. The findings of this study are that PT BPR X is in a position to support an aggressive strategy. where this is used as a guideline for several strategies in the 4 (four) quadrants namely SO strategy, WO strategy, ST strategy and WT strategy